Coaches' evaluations of the utility of the Basic Performance Demand Model for Sport - Males, J. R.; Hudson, J.; Kerr, J. H. (Journal of Sport Psychology in Action, 2020)
The Performance Demand Model for Sport (PDM; Males, Hudson, & Kerr) is based on four psychological fundamentals: mastery motivation, decision making, execution, and teamship. Four elite coaches from canoe slalom, rugby sevens, rowing, and athletics evaluated the utility of the PDM model and later trialed it with elite athletes. Two sets of semi-structured interviews provided subjective statements that generally: (a) supported PDM process-based principles and (b) post-field trials, endorsed the PDM for elite athlete use. With one exception, coaches used the PDM with athletes in different ways, recommending customization, simplification, and a focus on specific training contexts to enhance utility.